FAKTOR PENYEBAB RENDAHNYA MOTIVASI BELAJAR PESERTA DIDIK DI SMP NEGERI 10 SIJUNJUNG - Firsal, Firsal; Kasih, Fitria; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
This research was stimulated by the background of studentâs lower learning motivation at SMPN 10 Sijunjung. A learning motivation of students was influenced by internal and external factors. Internal factors come from students its self consisted their needs, eager, knowledge and aspiration, while external factors come from outside of students, consisted of teachers, environment and teaching strategy was implemented by teacher in the class in the form of reward and punishment, school equipment, friend, family and society. The aim of this research was to know internal and external factors due on the lower studentâs learning motivation at SMPN 10 Sijunjung.This research used descriptive, a study aim to describe the find of fact systematically, factual and accurate. The population of this research was all students at the class IX in SMPN 10 Sijunjung totally 221 people. Sample was taken by purposive random sampling totally 64 people. Technique of data collection used questionnaire data was distributed to respondents. To analysis the data used percentage analysis, counting the percentage of respondentsâ answer.Â From the result of research showed that internal factors caused the lower of studentâs motivation was in a lot category. While the external factors caused the lower of studentâs motivation was in a lot category. To be suggested to students to dig their potency and determine their aspiration that want to be reached in order always have high motivation in each following the learning process. To guiding teacher was expected to do any effort in handling internal and external problem due to lower motivation of students by creating funny teaching and to the next researcher was expected other factors related to reduce the studentâs learning motivation.